Laparoscopic or open treatment for hepatic alveolar echinococcosis: A single-institution experience. (June 2021) - Wan, Li; Ran, Bo; Aji, Tuerganaili; Shao, Yingmei; Jiang, Tiemin; Wen, Hao
Highlights: Radical resection is the best treatment for hepatic alveolar echinococcosis (AE). A laparoscopic approach has been used in the surgical treatment of hepatic AE. The laparoscopic approach is safe for radical resections in selected patients. Large, prospective, randomized trials are needed to confirm its superiority. Abstract: Objective: The aim of this study was to evaluate the safety and efficacy of laparoscopy in the treatment of hepatic alveolar echinococcosis (AE). Methods: Between January 2018 and December 2019, 213 hepatic AE patients were admitted to the authors' institution. Among them, 165 patients (77.46%, 165/213) underwent surgery. Of 13 patients who underwent laparoscopic treatment, two required conversion to open surgery. The remaining 11 patients (group 1) were analyzed. During the same period, 154 patients underwent open surgery, but only 14 records were compatible with the criteria for the laparoscopic approach and were reviewed retrospectively (group 2). Results: Conversion to open surgery occurred in two cases. Both groups were basically consistent in terms of detailed demographic data, characteristics of the lesions, and surgical strategy ( P > 0.05). The laparoscopic group not only achieved the same R0 resection as the open group, but the results were also significantly superior to those of the open group in terms of postoperative complications, postoperative catheterization time, and postoperative hospital stay ( P = 0.042, P = 0.046, and P = 0.045, respectively). No recurrences were observed in either group during this period. Conclusions: Laparoscopic surgery provides a safe and efficacious approach for hepatic AE in selected patients. Large, prospective, randomized trials are needed to confirm its superiority.